Occupational safety during interventions in confined spaces. (November 2015) - Burlet-Vienney, Damien; Chinniah, Yuvin; Bahloul, Ali; Roberge, Brigitte
Highlights: Study of fatal work accidents in confined spaces in Quebec between 1998 and 2011. Analysis of confined space risk management practices of 15 organizations. Identification of main risk factors present in fatal accidents. Identification of challenges associated with confined space risk management. Recommendations regarding preparation for and follow-up of confined space entries. Abstract: The aim of this study was to examine how organizations in Quebec manage risks associated with confined space interventions. Fatal work accidents that occurred in confined spaces in Quebec between 1998 and 2011 were therefore studied using the database of the provincial workers' compensation board. Thirty-two accident investigation reports involving 40 fatalities were obtained for the target period. The risk factors studied were the time of year, type of accident, and management and design problems. The risk management practices of 15 Quebec organizations were also analyzed through semi-structured interviews and observation of confined space interventions. Organizations with different profiles were chosen to cover a wide range of confined spaces and work situations. With respect to the regulatory in force in Quebec and based on the Canadian standard on the management of work in confined spaces, the organizations visited neglected the following points, in terms of both prescribed directives and actual practices: (i) management of subcontractors, (ii) auditing how risk reduction means are used, and (iii) integration of prevention through design. The lack of guidelines limited the real effectiveness of measures pertaining to training, rescue, use of certain control measures, and the preparation of entry permits. Given the complexity and diversity of the work involved in the issuance of permits, uncertainties during their preparation can lead to poor risk assessment and eventually to inadequate risk reduction measures. This article therefore proposes an entry permit consolidating all the information needed to prepare for entry, as well as recommendations regarding the aforementioned challenges.